Produção de astaxantina por Mucor javanicus (UCP 69), a partir de meio definido e utilizando resíduo industrial (milhocina e quirera de milho) - Silveira, Aline Alves Barbosa da (2007)
With the recent substitution of synthetic pigments for the natural carotenoids, research has been effected in the direction to make possible the production of these substances through alternative considered biological sources. In this work was studied the production of astaxanthin for the sample of Mucor javanicus (CPU - 69), using the media definite Hesseltine and Anderson (1957) modified by Andrade (2000) and using different corn waste media (corn steep liquor .CSL and .quirera.) in three different concentrations (4, 7 and 10%), pH 6,5, 120 rpm, 25ºC. It was analyzed, also, the influence of the time of culture of the sample (48h, 72h and 96 h) and the presence and absence of blue Light. To the ending of the fermentative process, the astaxanthin, was extracted in solution of Hexano/methanol (1: 1, v/v), centrifuged in 2000 rpm/10 minutes and analyzed by UV-visible spectrophotometry (470 nm). All the parameters studied in the experiments had been combined through a factorial design 33 and analyzed in Software Statistica 5,0. With Hesseltine and Anderson the condition that more favored the increase of the income of the astaxanthin was with in the time of 96h (26,7 g/g) in the absence of light and with the presence of light (37,7 g/g) increase almost 41%. With CSL the best condition for the production of the astaxanthin was with in the time of 96h (55,8 g/g) in the absence of light and with the presence of light (28,0 g/g) increase almost 100%. The .quirera. in the concentration of 7%, presented astaxanthin income better, in the time of 96h, with light (18,4 g/g) increase 37%, when compared with the cultures growth in the absence of light (13,4 g/g). The best income of astaxanthin with CLS and .quirera. was in the concentration of 7%, 96h, with light (33,8 g/g), increase almost 47% in when compared with the cultures growth in the absence of light (22,9 g/g). The concentrations that more favored the income of astaxanthin was: CSL 4%, .quirera. 7% and CSL with .quirera. 7%, both in the presence of blue light, demonstrate the blue light intervenes directly with the astaxanthin synthesis. Also, the wastes utilizes have been potential for the astaxanthin production. The analyses in Statistica 5,0, demonstrate that other studies are necessary for attainment of the maximum productivity of astaxanthin for M. javanicus, in alternative means.